Emerging drugs for the treatment of noninfectious uveitis. (3rd July 2019) - Pleyer, Uwe; Pohlmann, Dominika; Kardeş, Esra; Poddubnyy, Denis; Rademacher, Judith
ABSTRACT: Introduction : Uveitis is a leading cause of visual impairment and a significant burden of blindness. Although corticosteroids and conventional immunosuppressive agents have been successfully used, these are non-specific, and their long-term use may induce significant adverse effects. Areas covered : This article discusses existing local and systemic applied treatments for ocular inflammation including corticosteroids, non-biologic, and biologic disease-modifying anti-rheumatic drugs (DMARD). Potential drugs being studied in clinical trials are introduced for both local and systemic use. Expert opinion : Treatment options for uveitis continue to expand. Still, more efforts and research are needed to better understand the mechanisms potentially leading to clinical trials.